Fluctuations in muscle strength, shooting accuracy and serum hormone concentrations in conscripts during a 3-week combat training period - Igendia, Mikael (2015)
Conscripts and soldiers have to perform their duties in a multistressor environment. During prolonged periods of combat training, fluctuations in strength levels and hormone concentrations have been noted. However, there is limited information regarding the changes in shooting performance and whether changes in strength and hormonal concentrations are correlated with it. This study examined strength levels, shooting performance and hormonal fluctuations during a 3-week combat training period. Possible correlations between the variables were examined and investigated. This study lasted for 37 days and involved 49 Finnish male conscripts as subjects. The subjects acted as their own controls during the first 11 days of the study. The control period was followed by a shooting camp which lasted for 5 days, and it was the first part of the prolonged combat training period. The following eight days consisted of combat camp1 (CC1) and immediately after that combat camp 2 (CC2) which also lasted 8 days. After the prolonged combat training period subjects had 5 days to recover. Measurements were taken on day 1, day 7, day 23, day 32, and day 37. The measurements included isometric leg press and isometric bench press for measuring strength levels of the lower and upper body. Shooting performance was measured from a standing and prone position. Serum cortisol, testosterone, and SHBG concentrations were analyzed from blood samples collected in a fasted state between 6.30am -7.30 am. Significant fluctuations were observed in leg strength (p≤0.05) which decreased as loading was high, and after day 23 when loading was decreased, leg strength levels increased. The score from shooting in a standing position also decreased as the loading was high and as the loads began to decrease after day 23 the shooting standing score improved (p≤0.001). The shooting prone score did not show any significant changes throughout the study period. Serum cortisol concentrations increased significantly (p≤0.001) during the prolonged combat training period. Serum testosterone concentrations decreased (p≤0.001) during the prolonged combat training period. Significant positive correlations were observed in the changes in shooting standing scores and changes in strength levels for legs and upper body (r=0.33-r=0.46, p≤0.05˗ p≤0.001). After 5 days of recovery, all measured variables except cortisol returned to baseline levels. The present findings showed that significant fluctuations in the strength levels, serum hormone concentrations and shooting scores took place during the prolonged combat training period. Changes in strength levels and changes in shooting performance were related as well as changes in serum cortisol concentrations and shooting standing score. Thus, a prolonged combat training period may have adverse effects in strength levels and the shooting ability in soldiers. Therefore, it is important that soldiers get an appropriate amount of rest while performing their duties.